2017
DOI: 10.1080/24701394.2017.1325481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and genetic diversity of Aedes albopictus (Diptera, Culicidae) from China

Abstract: Aedes albopictus is one of the most invasive species, which can carry Dengue virus, Yellow fever virus and more than twenty arboviruses. Based on mitochondrial gene cytochrome c oxidase I (COI) and samples collected from 17 populations, we investigated the molecular character and genetic diversity of Ae. albopictus from China. Altogether, 25 haplotypes were detected, including 10 shared haplotypes and 15 private haplotypes. H1 was the dominant haplotype, which is widely distributed in 13 populations. Tajima'D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The same result for Chinese Ae. albopictus populations was also observed by both Guo et al and Zhang et al [79,80]. Guo dispersal from neighboring Southeast Asian countries may be the reason for the higher diversity of the Ae.…”
Section: Discussionsupporting
confidence: 53%
“…The same result for Chinese Ae. albopictus populations was also observed by both Guo et al and Zhang et al [79,80]. Guo dispersal from neighboring Southeast Asian countries may be the reason for the higher diversity of the Ae.…”
Section: Discussionsupporting
confidence: 53%
“…The same result for Chinese Ae. albopictus populations was also observed by both Guo et al and Zhang et al [79,80]. Guo et al identi ed three predominant haplotypes in Ae.…”
Section: Discussionmentioning
confidence: 64%
“…Few studies have reported the population structure and genetic diversity of Ae. albopictus in China, and they have focused on using mitochondrial DNA markers to analyze genetic diversity, regional structure, mainly in populations in southern China, or they have used a limited sampling size [31, 55]. For example, Guo et al [31] sequenced the mitochondrial DNA cytochrome c oxidase subunit 1 ( cox 1) gene of 140 Ae.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Guo et al [31] sequenced the mitochondrial DNA cytochrome c oxidase subunit 1 ( cox 1) gene of 140 Ae. albopictus from 14 populations in southern China, and Zhang et al [55] sequenced cox 1 of 119 Ae. albopictus from 17 populations in China.…”
Section: Discussionmentioning
confidence: 99%